SOCIAL JUSTICE AND BUDGET DISTRIBUTION: A CASE STUDY OF INEQUALITY IN THE ALLOCATION OF THE WADAS VILLAGE FUND BUDGET IN KARAWANG REGENCY TOWARD COMMUNITY WELFARE - Gumilar , Gun Gun; Saputri, Adelia; Dharma, Adji Satya; Yarullah, Esa Bintang (Prodi Ilmu Pemerintahan, Universitas AMIKOM Yogyakarta, 2024)
Social justice is the basis that the village government must fulfill towards its people, but the author found that there were deviations in budget distribution which affected the welfare of the community. Although many studies discuss budget inequality from an economic aspect, not many studies explore it from a social justice perspective. Qualitative methods are used through interviews and document analysis to understand how budget inequality influences community perceptions of social justice which aims to explore ethical values and principles of justice in budget decision making, as well as their impact on the welfare of village communities. The results of this research show that unequal budget allocation, especially in direct cash assistance programs, strengthens social and economic inequality at the village level, and raises critical questions about the government's role in realizing more inclusive social justice.